Effectiveness of Flipped Classroom in Enhancing Receptive Skills - Gillani, Syed Ahmad Raza Shah; Latif, Aimen; Gul, Naghma; Jabin, Bushra; Naz, Fakhar (Regional Lens, 2025)
The research was an experimental study that aimed to determine the efficacy of the flipped classroom model in the development of the receptive aspect of listening and reading among male students of F.Sc. Part I. To determine the effect of using the flipped classroom model during instruction on student performance in a classroom, a pretest-posttest control group design was used, whereby 44 students were randomly assigned either to an experimental (instructions were administered using the flipped classroom model) or control (instructions were administered using traditional lecture-based methods) group for a one-month intervention. The researcher used self-constructed tests to measure listening and reading skills. Data were analyzed using descriptive statistics (mean, standard deviation) and inferential statistics (independent samples t-test). The results indicated a significant difference in the post-test scores, leading to the rejection of the null hypotheses. The findings conclude that the flipped classroom model is more effective than traditional lectures in improving students’ listening and reading comprehension, providing valuable evidence for educators seeking to strengthen these foundational language abilities.